SUDEP classification: Discordances between forensic investigators and epileptologists. (16th October 2020) - Verducci, Chloe; Friedman, Daniel; Donner, Elizabeth J.; Laze, Juliana; Devinsky, Orrin
Abstract: We compared sudden unexpected death in epilepsy (SUDEP) diagnosis rates between North American SUDEP Registry (NASR) epileptologists and original death investigators, to determine degree and causes of discordance. In 220 SUDEP cases with post‐mortem examination, we recorded the epileptologist adjudications and medical examiner‐ and coroner‐ (ME/C) listed causes of death (CODs). COD diagnosis concordance decreased with NASR's uncertainty in the SUDEP diagnosis: highest for Definite SUDEP (84%, n = 158), lower in Definite Plus (50%, n = 36), and lowest in Possible (0%, n = 18). Rates of psychiatric comorbidity, substance abuse, and toxicology findings for drugs of abuse were all higher in discordant cases than concordant cases. Possible SUDEP cases, an understudied group, were significantly older, and had higher rates of cardiac, drug, or toxicology findings than more certain SUDEP cases. With a potentially contributing or competing COD, ME/Cs favored non–epilepsy‐related diagnoses, suggesting a bias toward listing CODs with structural or toxicological findings; SUDEP has no pathognomonic features. A history of epilepsy should always be listed on death certificates and autopsy reports. Even without an alternate COD, ME/Cs infrequently classified COD as "SUDEP." Improved collaboration and communication between epilepsy and ME/C communities improve diagnostic accuracy, as well as bereavement and research opportunities.